Daptomycin Induced Rhabdomyolysis and Subsequent Compartment Syndrome: : A Case Report - Esser, Katherine (Translation: The University of Toledo Journal of Medical Sciences, 2023)
Please view the PDF to see the formatted meeting abstract.